PENGARUH PERTUMBUHAN PENDUDUK, IPM, DAN PENGANGGURAN TERHADAP KEMISKINAN DI KABUPATEN/KOTA PROVINSI JAWA BARAT - Paramita Retno Indriati (2022)
Poverty is one of the backward conditions of human resources which causes a person's productivity to be low. If this happens in a sustainable manner, it will lead to high levels of poverty due to a person's inability to have capital to meet their daily needs. High poverty in West Java Province can be caused by several factors including population growth, HDI, and unemployment. This study aims to determine the effect of population growth, HDI, and unemployment on poverty in the Regency/City of West Java Province. The data used in this study were 27 regencies/cities in West Java Province for the period 2014-2020. The method used in this study is panel data regression analysis with the selected model, namely the Fixed Effect Model (FEM). This study shows that population growth has no effect on poverty, HDI has a significant negative effect on poverty, and unemployment has a significant positive effect on poverty.